Effects of walking football on adherence, safety, quality of life and physical fitness in patients with prostate cancer: Findings from the PROSTATA_MOVE randomized controlled trial - Capela, Andreia; Antunes, Pedro; Coelho, César André; Garcia, Catarina Laranjeiro; Custódio, Sandra; Amorim, Rui; Costa, Telma; Vilela, Eduardo; Teixeira, Madalena; Amarelo, Anabela; Silva, Joana; Joaquim, Ana; et al. (Frontiers in Oncology, 2023)
Aims To analyze the feasibility and impact of a walking football (WF) program on quality of life (QoL), cardiorespiratory fitness (CRF), muscle strength, and balance program in men with prostate cancer under androgen deprivation therapy (ADT). Methods Fifty patients with prostate cancer (stages IIb-IVb) under ADT were randomized to a 16-week WF program plus usual care (n=25) or usual care control group (n=25). The WF program consisted of three 90-minute sessions per week. Recruitment, withdrawal, adherence, enjoyment rate, and safety of the intervention were recorded throughout the study. Cardiorespiratory fitness was assessed before and after the interventions, while handgrip strength, lower limb muscle strength, static balance, and QoL were assessed before, during (week 8), and after (week 16) the interventions. Adverse events during sessions were also recorded. Results The WF group showed high levels of adherence (81.6 ± 15.9%) and enjoyment rate (4.5 ± 0.5 out of 5 points). In the intention-to-treat analysis, the WF group showed an improvement in chair sit-to-stand (p=0.035) compared to the control group. Within-group comparisons showed that handgrip strength in the dominant upper limb (p=0.024), maximal isometric muscle strength in the non-dominant lower limb (p=0.006), and balance in the dominant limb (p=0.009) improved over time in the WF group but not in the usual care group. The results obtained from the per-protocol analysis indicate that CRF improved significantly in the WF group as compared to the control group (p=0.035). Within-group analysis revealed that CRF (p=0.036), muscle strength in dominant (p=0.006) and non-dominant (p=0.001) lower limbs, and balance in the non-dominant lower limb (p=0.023) improved after 16 weeks of WF, but not in the control group. One major traumatic injury (muscle tear) was reported with a complete recovery before the end of the intervention. Conclusion This study suggests that WF is feasible, safe, and enjoyable in patients with prostate cancer under hormonal therapy. Furthermore, patients who adhere to the WF program can expect cardiorespiratory fitness, muscle strength, and balance improvements. Clinical trials registration clinicaltrials.gov, identifier NCT04062162.